Resveratrol-Loaded Levan Nanoparticles Produced by Electrohydrodynamic Atomization Technique - TOKSOY ÖNER, EBRU; GÜNDÜZ, OĞUZHAN (MDPI, 2021)
Considering the significant advances in nanostructured systems in various biomedical applications and the escalating need for levan-based nanoparticles as delivery systems, this study aimed to fabricate levan nanoparticles by the electrohydrodynamic atomization (EHDA) technique. The hydrolyzed derivative of levan polysaccharide from Halomonas smyrnensis halophilic bacteria, hydrolyzed Halomonas levan (hHL), was used. Nanoparticles were obtained by optimizing the EHDA parameters and then they were characterized in terms of morphology, molecular interactions, drug release and cell culture studies. The optimized hHL and resveratrol (RS)-loaded hHL nanoparticles were monodisperse and had smooth surfaces. The particle diameter size of hHL nanoparticles was 82.06 & PLUSMN; 15.33 nm. Additionally, release of RS from the fabricated hHL nanoparticles at different pH conditions were found to follow the first-order release model and hHL with higher RS loading showed a more gradual release. In vitro biocompatibility assay with human dermal fibroblast cell lines was performed and cell behavior on coated surfaces was observed. Nanoparticles were found to be safe for healthy cells. Consequently, the fabricated hHL-based nanoparticle system may have potential use in drug delivery systems for wound healing and tissue engineering applications and surfaces could be coated with these electrosprayed particles to improve cellular interaction.
Keywords: Halomonas levan; polymeric nanoparticles; resveratrol; electrohydrodynamic atomization; drug delivery systems; DRUG-DELIVERY; HALOMONAS-SMYRNENSIS; BIOAVAILABILITY; MICROPARTICLES; ENCAPSULATION; SOLUBILITY; STABILITY; HYDROGELS; FILMS